Death in Paradise. Season eight [videorecording (DVD)] - Svaasand, Stewart; O'Gorman, Sarah; O'Hanlon, Ardal; Jobert, Joséphine, 1985-; Bakare, Tobi (BBC, 2019)
A British cop is out of his element after he is sent to the tiny island of Sainte Marie to solve a murder case.